2001
DOI: 10.1046/j.1523-1755.2001.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of complement C5a receptor mRNA in human diseased kidney assessed by in situ hybridization

Abstract: Our results indicate that renal cells produce C5aR and that activation of C5a/C5aR pathway on renal cells may be involved in tissue injury in mesGN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 42 publications
5
48
0
2
Order By: Relevance
“…The renal distribution of the C3aR is similar to that reported for C5aR (22,23,25). In regard to C5aR, published reports indicate that the pattern of expression of this receptor is altered in disease states with up-regulation in glomerular mesangial cells (26). This finding suggests that further investigation into the distribution of the C3aR in pathologic conditions is warranted.…”
Section: Discussionsupporting
confidence: 77%
“…The renal distribution of the C3aR is similar to that reported for C5aR (22,23,25). In regard to C5aR, published reports indicate that the pattern of expression of this receptor is altered in disease states with up-regulation in glomerular mesangial cells (26). This finding suggests that further investigation into the distribution of the C3aR in pathologic conditions is warranted.…”
Section: Discussionsupporting
confidence: 77%
“…These include immune complexinduced peritonitis [30], experimental arthritis [31], sepsis [32] and anti-phospholipid syndrome [33]. C5aR mRNA has been found to be up-regulated in glomeruli of patients with lupus nephritis, supporting its relevance in the human disease [20]. Here we have shown that the overexpression of both C5aR mRNA and protein in MRL/ lpr mouse kidneys started before the onset of detectable disease, and increased as autoimmune disease progressed, suggesting a potential role for C5a and C5aR signals in the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 97%
“…Of relevance to the kidney is the finding of C5aR in cultured renal mesangial and proximal tubular epithelial cells [16][17][18], and that C5a signaling through C5aR has been shown to be important in the tubulointerstitial injury in a model of immune complex-mediated glomerulonephritis (GN) [19]. As for humans, the expression of C5aR has been observed to be increased in the kidneys of patients with lupus nephritis [20], supporting its potential relevance in disease pathogenesis. Yet, direct studies on the role of C5a and C5aR in the pathogenesis of lupus nephritis have not been performed.…”
Section: Introductionmentioning
confidence: 97%
“…C5aR expression in the skin lesions of patients with systemic sclerosis suggests an activation of pathways that end up with a growth factor-dependent matrix synthesis (31). In mesangial proliferative glomerulonephritis, the glomerular expression of C5aR mRNA and protein correlate positively with the extent of mesangial hypercellularity and mesangial matrix expansion (32). In rheumatoid arthritis, i.e., another condition with inflammatory and proliferative stages, some chondrocytes express C5aR (33, 34) that argues for a contribution of this receptor in arthritis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%